2019
DOI: 10.1002/ijgo.12935
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing abdominal sacrocolpopexy for the treatment of apical prolapse: One year on

Abstract: Objective To determine the safety and efficacy of a standardized bilateral abdominal sacrocolpopexy using polyvinylidene fluoride mesh 1‐year post‐operatively. Methods In a retrospective observational study of women undergoing bilateral abdominal sacrocolpo/cervicopexy between July 2013 and October 2016 at the Norfolk and Norwich University Hospital, Norwich, UK, patients were assessed 1 year post‐operatively using the International Consultation on Incontinence Questionnaire—Vaginal Symptoms (ICIQ–VS). Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
(48 reference statements)
0
4
0
Order By: Relevance
“… 22 Likewise, a case series study carried out in the UK reported a lower wound infection rate of 2%. 23 This is an alarming situation that requires further investigation. Within the first 12 months of follow-up, none of our patients experienced gastrointestinal issues that required a readmission, surgery, or hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Likewise, a case series study carried out in the UK reported a lower wound infection rate of 2%. 23 This is an alarming situation that requires further investigation. Within the first 12 months of follow-up, none of our patients experienced gastrointestinal issues that required a readmission, surgery, or hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The most common limiting factor, i.e., failure mode, was a mesh failure for group 1 and group 2, so that the fixation itself supported more load than the PVDF-tape. Literature does not report about any mesh erosion after PVDF-tape fixation with sutures after bilateral cervicosacropexy [ 15 , 18 , 19 , 26 ]. So from a clinical point of view, the factor “mesh failure” does not seem to have any influence on the surgical results, because follow-ups four months after surgery showed only a relapse of apical prolapse because of an insufficient cervical fixation, but all further patients had an apical POP-Q stage 0, which means that the right anatomical position could be restored and the mesh was still intact [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Jäger et al [ 11 ] and other study groups [ 18 , 19 ] in laparoscopic approach, three instead of four interrupted sutures were used to fix the central part of the PVDF-tape on the cervix or the vaginal vault (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since laparoscopic suturing prolongs the operation time in laCESA or laVASA compared to the use of the fixation device with titanium tacks, the question arose if there are comparable results between the sutures, which are used as standard by Jäger et al [ 10 ] and other study groups [ 16 , 17 ] and the ProTack™ tacks and if one fixation method is superior. Moreover, the aim of this study was to find out, if there is a difference depending on how the tacks are arranged.…”
Section: Introductionmentioning
confidence: 99%